A General One‐Pot Methodology for the Preparation of Mono‐ and Bimetallic Nanoparticles Supported on Carbon Nanotubes: Application in the Semi‐hydrogenation of Alkynes and Acetylene. Issue 35 (22nd May 2019) - Lomelí‐Rosales, Diego A.; Delgado, Jorge A.; Díaz de los Bernardos, Miriam; Pérez‐Rodríguez, Sara; Gual, Aitor; Claver, Carmen; Godard, Cyril
Abstract: A facile and straightforward methodology for the preparation of monometallic (copper and palladium) and bimetallic nanocatalysts (NiCu and PdCu) stabilized by a N‐heterocyclic carbene ligand is reported. Both colloidal and supported nanoparticles (NPs) on carbon nanotubes (CNTs) were prepared in a one‐pot synthesis with outstanding control on their size, morphology and composition. These catalysts were evaluated in the selective hydrogenation of alkynes and alkynols. PdCu/CNTs revealed an efficient catalytic system providing high selectivity in the hydrogenation of terminal and internal alkynes. Moreover, this catalyst was tested in the semi‐hydrogenation of acetylene in industrially relevant acetylene/ethylene‐rich model gas feeds and showed excellent stability even after 40 h of reaction. Abstract : Working alone and together : A facile and straightforward methodology for the preparation of monometallic (copper and palladium) and bimetallic nanocatalysts (NiCu and PdCu) stabilized by a N‐heterocyclic carbene ligand is reported. Both colloidal and supported nanoparticles (NPs) on carbon nanotubes (CNTs) were prepared and tested for selective hydrogenations of alkynes and alkynols.